Integrity of Best-Answer Assignments in Large Enrollment Classes; the role of Compulsory Attribution - Kurt Schmitz; Veda Storey (Journal of Teaching and Learning with Technology)
Many instructional methods that focus on skill and competency development have a single or small set of appropriate answers. Best-answer assignments are popular among instructors of large enrollment classes due to the relative ease with which scoring, and feedback, can be managed at scale. However, cheating is regularly confirmed at disturbingly high levels, and commonly used content comparison tools are unsuited to identify original authors of best-answer assignments. This research presents a method to enforce compulsory attribution as a countermeasure to enhance the integrity of best-answer digital assignments. The method secures compulsory attribution of digital solutions using meta-data, access controls, and extensible code available in many common applications, including Microsoft Office. A unique feature that makes this method well-suited to large enrollment classes is the ability to secure and, when necessary, to delete stolen work, thereby precluding misappropriation. This method minimizes the bureaucratic burdens associated with academic dishonesty procedures. This study, grounded in Routine Activities Theory, describes a compulsory attribution method, called StartHere, that activates perceived guardianship in the form of interpersonal technical controls and social ties controls for offline digital assignments. A field experiment collects, analyzes, and reports empirical data in the form of qualitative student comments, quantitative survey data, and actual misappropriation events. The findings demonstrate efficacy of both guardianship pathways within large enrollment classes.